Giant intrapulmonary solitary fibrous tumor - Sheela Devi Chandakavadi Shivalingaiah; Deepika Gurumurthy; Gauri Dadich (University of São Paulo, 2024)
Solitary fibrous tumor (SFT) is a soft tissue tumor of mesenchymal origin involving, most commonly, the pleura. Intrapulmonary SFT is a slow-growing tumor that rarely reaches giant forms. SFTs are asymptomatic and often randomly discovered by routine chest X-rays. The diagnosis requires histopathological and immunohistochemical (IHC) examinations. Most of the SFTs are benign and present an indolent course. Larger tumors are more likely to be malignant and consequently associated with a worse prognosis. Despite having histopathological criteria for malignancy, the behavior of SFTs is challenging to predict. We report a case of giant intrapulmonary SFT of intermediate risk.